Hiwalah Sebagai Solusi Dalam Mengatasi Kredit Macet Dalam Perbankan Syariah - Syahpawi Syahpawi (LPPM ISNJ Bengkalis, 2012)
This article talks about Hiwalah as the solution in overcoming credit insurance problem in banking syariah. Hiwalah is a transfer of debt from man is owing to others which to pay for it. This thing doesn't close the possibility that this exercise can be done in the banking world especially relates to bad debt. To overcome bad debt if the pawn was cooperative ownership possession happened bad debt in credit, hence can be transferred to capable to account it with the possession pawn makes a move to the underwriter. Even is side is other can also for others which wish to continue defrayal stucking the with possession which financed is pawn then happened usage sweetener to the underwriter.